Greenhouse testing of new wheat cultivars compared to those with known drought tolerance - Gáspár, László (Acta Biologica Szegediensis, 2005)
Drought causes huge losses in crop production. With global climatic changes in prospect the extension of drought-prone areas is likely to grow in the future which will require the growing of drought resistant cultivars. In this study some physiological parameters of newly bred Hungarian cultivars were compared with those of drought tolerant or sensitive cultivars. The connection of these physiological parameters to the yield of the cultivars was also evaluated. Drought treatment decreased soil water content from 49-55% (control) to 13-17% (treated) of its water-holding capacity. As a result, there was a significant increase in midday water saturation deficiency (from 10-20% in control plants to 30-45% in treated ones) and a parallel decrease in transpiration rates and net CO2 assimilation. Analysis of averaged data of 3 consecutive years suggests that there is some correlation between net CO2 assimilation and sugar accumulation in flag leaves during the grain filling period with the yield of the different cultivars, however, there are other important factors influencing the yield which were not analysed in this study. The lowest yield reduction was found in Gk Pántlika, Mv Mariska, Mv Mambo and Mv Emese (7-10%), which proved to be drought tolerant cultivars from an agronomical point of view.